Influence of Dry Beach on the Dynamic Stability of Ash Storage Field: A Numerical Analysis. (20th February 2021) - She, Fangtao; Liu, Chang; Zhou, Xiangang; Qi, Changjun; Ding, Jiulong
Abstract : Ash storage sites are a commonly used method of disposing fly ash, a byproduct of coal combustion, in China today, and when it accumulates to a certain height, serious geological hazards may occur as a result of seismic activity. In this study, an in situ standard penetration test was carried out on a constructed ash storage site in Northwest China to evaluate the potential for liquefaction of alluvial fly ash within the site, and the results show that dynamic liquefaction can occur within a newly constructed three-stage subdam. A numerical analysis of the influence of dry beach length on the dynamic response of the primary dams and subdams and an assessment of the extent of dynamic liquefaction in the ash storage field were carried out using the Wenchuan seismic waves as input ground motion. Numerical results prove that the acceleration within the ash storage field is relatively low in the original breccias layer and gradually increases with height, with the peak acceleration occurring in the vicinity of the third subdam and a decreasing trend from the subdams towards the ash storage field. As the length of the dry beach increases, the Peak accelerations in the ash storage area occur near the third subdams at larger dry beach length. Meanwhile, the acceleration in the ash storage area close to the surface gradually increases, and, significantly, the range where higher accelerations occur also becomes larger. The maximum horizontal displacements at different dry beach lengths occur at the crest of the third subdam and in the adjacent ash storage area. As the length of the dry beach increases, the maximum horizontal displacements show a certain decrease, but they occur progressively further away from the third subdam, so that, under dynamic action, the dams become safer. The extent of liquefaction decreases at larger dry beach length and extends further away from the third subdam into the ash storage area. It is, therefore, recommended that the length of the dry beach should not be less than 150 m for this ash storage site.